Towards an “Ecumenical” Council Inside of Orthodoxy! - Nicu Dumitrașcu (Religions, 2023)
Ecumenism is a recurrent theme in Orthodox theological debates, but the syntagma “Orthodox ecumenism” is rarely used because it seems to be very restrictive and inappropriate. However, in exceptional situations, such as a war between two Orthodox peoples, I think it might be more than necessary. In the first part of this essay, I will discuss how the mirage of a “third” Rome and the partnership with the Kremlin makes the Russian Church an adversary of ecumenism inside of Orthodoxy. Any Church that blesses a war, aggression, and confrontation and shows imperial tendencies is excluded de facto from the communion with other Churches. In the second part of my work, I will analyze the consequences of the “schism” created by Patriarch Kirill in the bosom of Orthodoxy. What were (or what were not!) the positions of other Orthodox Churches when Patriarch Kirill blessed the war and betrayed the principles of the Gospel of Christ? Why is there a need for a so-called “Ecumenical Orthodox Council” and what are the chances of this happening?